Glioblastoma multiforme: novel therapeutic targets. (2nd July 2020) - Muir, Matthew; Gopakumar, Sricharan; Traylor, Jeffrey; Lee, Sungho; Rao, Ganesh
ABSTRACT: Introduction: The increasingly detailed genetic characterization of glioblastoma (GBM) has failed to translate into meaningful breakthroughs in treatment. This is likely to be attributed to molecular heterogeneity of GBM. However, the understanding of the tumor microenvironment in GBM has become more refined and has revealed a wealth of therapeutic targets that may enable the disruption of angiogenesis or immunosuppression. Areas covered: This review discusses the selective targeting of tumor-intrinsic pathways, therapies that target the GBM tumor microenvironment and relevant preclinical studies and their limitations. Relevant literature was derived from a PubMed search encompassing studies from 1989 to 2020. Expert opinion: Despite appropriate target engagement, attempts to directly inhibit oncogenic pathways in GBM have yielded little success. This is likely attributed to the molecular heterogeneity of GBM and the presence of redundant signaling that allow for accumulation of adaptive mutations and development of drug resistance. Subsequently, there has been a shift toward therapies modulating the pro-angiogenic, immunosuppressive tumor microenvironment in GBM. The non-transformed cells in the microenvironment which includes endothelial cells, myeloid cells, and T cells, are presumably genetically stable, less susceptible to heterogeneity, and easier to target. This approach offers the highest potential for a therapeutic breakthrough in GBM.